The Role of Teacher Training Programs in Enhancing Educational Quality in Bangladeshi Schools - Elias Ahmed (Walidem International Journal of Community Engagement, 2025)
Objective: This study investigates the role of teacher training programs in improving educational quality in Bangladeshi schools, with a focus on their impact on teaching practices, classroom management, and student engagement. Theoretical framework: The study is based on the theory of teacher professional development, which posits that continuous training improves teaching effectiveness, leading to better student outcomes. Literature review: Teacher training improves teaching quality and student outcomes, but challenges like limited resources and poor implementation hinder effectiveness. Tailored programs, especially in rural areas, and technology integration are crucial for success. Methods: A mixed-methods approach was employed, combining quantitative surveys and qualitative interviews. Data were collected from 100 schools across both urban and rural areas of Bangladesh. Teachers and administrators provided feedback on their experiences with training programs and their impact on teaching and student performance. Results: The findings indicate that teacher training programs significantly improve teaching practices, with most teachers reporting enhanced classroom management and increased student engagement. However, challenges such as limited resources, lack of ongoing support, and accessibility issues in rural areas were identified as barriers to the success of these programs. Implications: The results highlight the need for more context-specific and sustainable teacher training initiatives. Policymakers should prioritize continued professional development, particularly in rural regions, to ensure long-term improvements in educational quality. Novelty: This study provides new insights into the effectiveness of teacher training programs in Bangladesh, emphasizing the importance of sustained and tailored professional development.